A psychopath among us: literature review (Research, Society and Development, 2022)
Objective: to elucidate the signs of a psychopathic mind and describe the experiences lived by three victims; whose lives have suffered voracious devastation as a result of encountering some of these beings. Methodology: Online searches were carried out for the construction of this article, which included the Web of Science databases, PUBMED Central, BVS / BIREME, Science Direct, The Cochrane Library and also PROSPERO. Results: Psychopaths are people who lack empathy, remorse, or any sense of mindfulness. Their lives are based on controlling the people they live with, taking from them everything they can, and when they are no longer needed, discarding them. The emotional, psychological and financial damage is often enough to devastate a person for life, and in some cases lead to death. Conclusions: Psychopaths are among us and there is no cure for this personality disorder. The treatment must be directed towards the victims, so that they are aware that these people exist so that they can be prevented or detected as soon as possible.